Anthocran® Phytosome®: Prevention of Recurring Urinary Infections and Symptoms after Catheterization. (2nd January 2023) - Cotellese, Roberto; Ledda, Andrea; Belcaro, Gianni; Cesarone, Maria R.; Scipione, Claudia; Scipione, Valeria; Dugall, Mark; Feragalli, Beatrice; Riva, Antonella; Allegrini, Pietro; Petrangolini, Giovanna; Togni, Stefano
Abstract: In this preliminary pilot registry study, we investigated the effects of the oral supplementation of a standardized cranberry extract (Anthocran® Phytosome®, Indena) delivered by a lecithin-based system, for the prophylactic management of recurrent-urinary tract infections (R-UTIs). We included 64 otherwise healthy subjects who underwent a surgical procedure and required post-surgical urinary catheterization for high-risk UTIs or a previous history of R-UTIs. Patients were given supplementation with the standardized cranberry extract at the dose of either 120 mg/day ( n  = 12) or 240 mg/day ( n  = 12) or assigned to a control group consisting of standard management (SM; n  = 18) or nitrofurantoin administration ( n  = 22) for 4 weeks. After 4 weeks, patients receiving the standardized cranberry supplementation reported to have a more effective reduction in UTI symptoms, as assessed on the visual analogue scale, compared with patients in the SM or nitrofurantoin groups. The occurrence of hematuria and urine bacterial contamination were decreased among patients treated with the supplement compared with controls ( p  < 0.05). The cranberry extract was also superior to the control management in terms of recurrence of signs/symptoms, with none of the patients in this group suffering from a R-UTI in the 3 months following the study end ( p  < 0.05). The supplementation showed an optimal safety profile, with no significant adverse events and no drop-outs in the supplement group. This registry shows that this cranberry extract is effective as a supplementary, preventive management in preventing post-operative, post-catheter UTIs; the product has a good tolerability profile.